Evaluation of nanoparticle albumin-bound paclitaxel loaded macrophages for glioblastoma treatment based on a microfluidic chip - Xie, Zuorun; Ye, Junyi; Gao, Xinghua; Chen, Hang; Chen, Maosong; Lian, Jiangfang; Ma, Jingyun; Wang, Hongcai (Frontiers in Bioengineering and Biotechnology, 2024)
Glioblastoma (GBM), recognized as the most aggressive primary brain tumor, presents a formidable challenge in achieving complete surgical resection. Given the phagocytic function, inherent migratory capacity, deep tissue penetration, and potential for cell therapy, macrophages (MΦ) have been extensively investigated for their role in tumor treatment. Here, we developed a novel approach utilizing MΦ for the delivery of nanoparticle albumin-bound paclitaxel (nab-PTX), resulting in the formation of nab-PTX/MΦ. It is worth noting that the nab-PTX/MΦ exhibited the M1 phenotype, which inhibits tumor progression. To mimic the conditions of the blood-brain barrier and solid GBM tumor, we co-cultured human umbilical vein endothelial cells and GBM cells in a microfluidic chip. This study innovatively utilized the three-dimensional microfluidic model to assess the anti-GBM effect of nab-PTX/MΦ. Our findings demonstrated that the nab-PTX/MΦ exerted a significant anti-GBM effect compared to the individual administration of nab-PTX or MΦ, thereby presenting the potential of MΦ as drug delivery vectors for GBM therapy. Furthermore, this study provided a potential ex vivo platform for the advancement of innovative cell-based therapies and tailored therapeutic strategies for GBM.